THE EFFECT OF GROUP INVESTIGATION MODEL ON CONCEPTUAL KNOWLEDGE ONTEMPERATURE AND HEAT MATERIALS IN CLASS XI SMK MUHAMMADIYAH 8 MEDAN - Dian Kumala Sari; Muhammad Kadri (Universitas Negeri Medan, 2018)
The objective of this research is to know the conceptual knowledge of the students using cooperative learning model of group investigation type toward conceptual knowledge on the subject matter of temperature and heat in class XI semester I SMK Muhammadiyah 8 Medan T.P. 2017/2018. The research type is quasi experiment with pretest-postes design. The population of the study were all students of class XI SMK Muhammadiyah 8 Medan. The research sample consisted of 2 classes determined by cluster random sampling technique. Class XI TKJ - 1 as experimental class by applying cooperative learning model type investigation and class XI TKJ - 2 as control class by applying conventional learning model. The instrument used in this study is the test of cognitive learning outcomes in the form of multiple choice which is accompanied by observation of student activity. Based on the results of pretest data processing using different test, the value of both classes at the significant level α = 0.05 concluded there is no significant difference from the value of pretes of both classes, meaning that the two classes have the same initial ability. Furthermore the two classes are treated differently, after the learning is completed in both classes is done postes. Based on the results of hypothesis testing with a significant level of 0.05 concluded that there is a difference in conceptual knowledge due to the influence of cooperative learning model type group investigation of conceptual knowledge on the subject matter of temperature and heat in class XI semester I SMK Muhammadiyah 8 Medan